Unusual Presentation of Hypothyroidism in a Pregnant Woman, Mimicking Gestational Trophoblastic Neoplasm - Soheila Aminimoghaddam; Narmin Karisani; Maryam Mazloomi; Maryam Rahimi (Case Reports in Oncological Medicine)
Hypothyroidism is a common health issue worldwide with varying clinical manifestations. We report a woman who experienced an incomplete abortion and undiagnosed hypothyroidism who was referred to the oncologist with the suspicion of metastatic gestational trophoblastic neoplasm (GTN). A 29-year-old woman with incomplete abortion was referred to an oncologist for possible GTN due to persistent active vaginal bleeding, an elevated beta human chorionic gonadotropin (hCG), abnormal cervical inspection exam, abnormal liver function tests, ovarian enlargement, ascites, and a pleural effusion. She was found to have hypothyroidism in further work-up. She was managed with thyroid hormone replacement therapy and her condition improved after 6 weeks. Complete resolution of the ovarian mass and pericardial and pleural effusion was achieved. This case describes an important experience; hypothyroidism should be considered in the differential diagnosis of any woman with an incomplete abortion presenting with an ovarian mass. Evaluation and correct diagnosis are important to prevent mismanagement.